Overexpression of Phosphomimic Mutated OsWRKY53 Leads to Enhanced Blast Resistance in Rice - Chujo, Tetsuya (Public Library of Science, 2014)
WRKY transcription factors and mitogen-activated protein kinase (MAPK) cascades have been shown to play pivotal roles in the regulation of plant defense responses. We previously reported that OsWRKY53-overexpressing rice plants showed enhanced resistance to the rice blast fungus. In this study, we identified OsWRKY53 as a substrate of OsMPK3/OsMPK6, components of a fungal PAMP-responsive MAPK cascade in rice, and analyzed the effect of OsWRKY53 phosphorylation on the regulation of basal defense responses to a virulence race of rice blast fungus Magnaporthe oryzae strain Ina86-137. An in vitro phosphorylation assay revealed that the OsMPK3/OsMPK6 activated by OsMKK4 phosphorylated OsWRKY53 recombinant protein at its multiple clustered serine-proline residues (SP cluster). When OsWRKY53 was coexpressed with a constitutively active mutant of OsMKK4 in a transient reporter gene assay, the enhanced transactivation activity of OsWRKY53 was found to be dependent on phosphorylation of the SP cluster. Transgenic rice plants overexpressing a phospho-mimic mutant of OsWRKY53 (OsWRKY53SD) showed further-enhanced disease resistance to the blast fungus compared to native OsWRKY53-overexpressing rice plants, and a substantial number of defense-related genes, including pathogenesis-related protein genes, were more upregulated in the OsWRKY53SD-overexpressing plants compared to the OsWRKY53-overexpressing plants. These results strongly suggest that the OsMKK4-OsMPK3/OsMPK6 cascade regulates transactivation activity of OsWRKY53, and overexpression of the phospho-mimic mutant of OsWRKY53 results in a major change to the rice transcriptome at steady state that leads to activation of a defense response against the blast fungus in rice plants.